1997
DOI: 10.1099/0022-1317-78-4-873
|View full text |Cite
|
Sign up to set email alerts
|

Complete DNA sequence of canine adenovirus type 1.

Abstract: The complete DNA sequence of a field strain of canine adenovirus type 1 was determined by sequencing random fragments of viral DNA cloned into pBluescript. The virus has a genome of 30 536 bp flanked by two identical 161 bp inverted terminal repeats. Thirty ORFs have been identified, based on genomic location or sequence identity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 20 publications
3
38
1
1
Order By: Relevance
“…Finally, we wished to evaluate the hepatotropism of Ad5Luc1-CK1, since CAV-1 has been reported to rarely cause hepatitis in dogs. 32 Importantly, our data showed that liver transduction of Ad5Luc1-CK1 was significantly lower compared to Ad5Luc1.…”
Section: Novel Expanded Tropism For Cancer Gene Therapy Ma Stoff-khalmentioning
confidence: 68%
See 2 more Smart Citations
“…Finally, we wished to evaluate the hepatotropism of Ad5Luc1-CK1, since CAV-1 has been reported to rarely cause hepatitis in dogs. 32 Importantly, our data showed that liver transduction of Ad5Luc1-CK1 was significantly lower compared to Ad5Luc1.…”
Section: Novel Expanded Tropism For Cancer Gene Therapy Ma Stoff-khalmentioning
confidence: 68%
“…In this regard, there are two canine isolates, serotypes 1 and 2, which may offer novel adenovirus infection pathways. 32 CAV-2 is one of the few non-human adenoviruses that have been investigated as a gene transfer vector for human applications. Particularly, a replicationdeficient CAV-2 vector has been constructed 14,16,33 and displayed a distinct tropism not exhibited by human Novel…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another region needed to be amplified to obtain a phylogenetic tree confirming it. The gene regions (E1, E2, E3 and E4) of CAV-2 are responsible for efficient replication of the virus, viral gene expression and regulation of host-cell functions (MORRISON et al, 1997). Nine different amino acids have been identified on the molecular level (amino acid differences) between the China-Turkey isolates subgroup and the America-Europe subgroup strains.…”
Section: Discussionmentioning
confidence: 99%
“…CAV-1 and CAV-2 were found to be genetically different by restriction endonuclease analysis [10,75] and by DNA hybridization [106]. The complete sequence analysis of both the CAV-1 and CAV-2 genome has revealed about 75% nucleotide identity [49,114]. Although CAV-1 and CAV-2 are related genetically and antigenically [109,168], they have different tissue tropism.…”
Section: Canine Adenovirus Typementioning
confidence: 99%